Comorbidity and adverse events in acquired hemophilia A: data from the GTH-AHA-EMI study - Christian Herbert Burgmann; Ulrich J. Sachs; Karolin Trautmann-Grill; Christian Pfrepper; Paul Knöbl; Richard Greil; Johannes Oldenburg; Wolfgang Miesbach; Katharina Holstein; Hermann Eichler; Patrick Möhnle; Matthias Höpting; et al. (Research and Practice in Thrombosis and Haemostasis)
Background: Persons with acquired hemophilia A are often older and suffer from comorbidity or frailty. Little is known about the impact on clinically relevant outcomes of acquired hemophilia A. Objectives: To assess the relevance of age, physical performance status, comorbidity, and concomitant medication on the risk of bleeding and other outcomes. Methods: Post hoc analysis of data from the GTH-AHA-EMI study that used emicizumab for bleed protection and withheld immunosuppressive treatment during the early phase of management. Primary endpoint was the rate of clinically relevant new bleeding (CRNB) during the first 12 weeks of emicizumab prophylaxis. Results: Forty-seven patients were enrolled. Median age was 76 years; performance status (World Health Organization performance status [WHO-PS]) was 3 or worse in 41%; Charlson comorbidity index (CCI) was 5 or higher in 63%; antithrombotic drugs were reported in 34%. Rate of CRNB during 12 weeks of emicizumab prophylaxis was similar across subgroups of age, sex, WHO-PS, CCI, baseline factor VIII activity, and inhibitor titer. Patients with CRNB during the study had more severe anemia already at baseline. However, persistent severe anemia in week 4 was not related to risk of bleeding beyond this time. CRNB was associated with injury from falling in 7 of 14 patients. Adverse events grade 3 or higher were not related to baseline CCI or age but were more frequent in patients with poor WHO-PS. Conclusion: Emicizumab provided bleed protection regardless of age and comorbidity. Clinical baseline characteristics did not predict breakthrough bleeding under emicizumab. Poor WHO-PS at baseline was associated with severe adverse events during the study.